The Role of Cost Accounting Information in Enhancing Firm Value and Stakeholder Responsibility: Evidence from Indonesia’s Cement Industry - Hardana, Ali; Zaini, Zaki; Husen Subana, Dadang; Wahyu Utami, Try (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study examines the effect of cost accounting information on the increase in company value and the fulfillment of stakeholder responsibilities in cement companies listed on the Indonesia Stock Exchange (IDX) during 2016–2021. Research Methods: The research uses simple linear regression for causality testing, one-way ANOVA, and independent sample tests for comparative analysis, with a 5% significance level. Results: The findings show that cost accounting information significantly affects firm value, particularly in calculating cost of goods manufactured. Higher firm value improves the company's ability to meet its obligations to stakeholders, including paying dividends to shareholders, covering loan interest to creditors, paying salaries to employees, and fulfilling tax responsibilities to the government. Conclusion: The study also identifies significant differences among public cement companies regarding firm size, dividend payments, tax burden, and interest expenses. However, salary expenses did not show significant differences. These results highlight the strategic importance of accurate cost accounting in enhancing financial performance and maintaining stakeholder trust.